Protein and Organic-Molecular Crystallography With 300kV Electrons on a Direct Electron Detector - Takaba, Kiyofumi; Maki-Yonekura, Saori; Inoue, Satoru; Hasegawa, Tatsuo; Yonekura, Koji (Frontiers in Molecular Biosciences, 2021)
Electron 3D crystallography can reveal the atomic structure from undersized crystals of various samples owing to the strong scattering power of electrons. Here, a direct electron detector DE64 was tested for small and thin crystals of protein and an organic molecule using a JEOL CRYO ARM 300 electron microscope. The microscope is equipped with a cold-field emission gun operated at an accelerating voltage of 300 kV, quad condenser lenses for parallel illumination, an in-column energy filter, and a stable rotational goniometer stage. Rotational diffraction data were collected in an unsupervised manner from crystals of a heme-binding enzyme catalase and a representative organic semiconductor material Ph-BTBT-C10. The structures were determined by molecular replacement for catalase and by the direct method for Ph-BTBT-C10. The analyses demonstrate that the system works well for electron 3D crystallography of these molecules with less damaging than using the conventional scintillator-coupled camera.